Initial effects of woody biomass removal and intercropping of switchgrass (Panicum virgatum) on herpetofauna in eastern north Carolina - Jessica A. Homyack; Zachary Aardweg; Thomas A. Gorman; David R. Chalcraft (Wildlife Society Bulletin)
Abstract Forests are potential sources for a wide range of alternative fuels, which could reduce dependency on fossil fuels and carbon emissions, but sustainability of producing biofuels from forests has not been well‐studied. Therefore, we investigated effects of woody biomass harvest, intercropping perennial grasses, and combinations of these treatments on herpetofauna in loblolly pine (Pinus taeda) plantations in a randomized and replicated field experiment in eastern North Carolina, USA. We sampled amphibians and small reptiles with drift fence arrays from April to July during 1 and 2 years after treatment establishment. We had 425 captures of 15 species of herpetofauna across the 2 sampling seasons, but did not observe large general effects of biomass removal or planting of switchgrass (Panicum virgatum) in pine plantations on detection, diversity, or relative abundance. However, planned contrasts indicated Simpson's index of diversity was greater in plots managed for switchgrass only compared with pine plantations during year 2, and that captures of southern toads (Anaxyrus terrestris) were less common in switchgrass plots than in pine plantations intercropped with switchgrass. Neither intercropping switchgrass with pine nor removal of harvest residuals caused herpetofauna diversity or abundance of common species to differ from traditional plantation management during the first 2 years following treatment establishment. With the exception of switchgrass‐only plots, which had lower herpetofauna species evenness, the potential practices we considered for biofuels production are unlikely to have short‐term effects on herpetofauna relative to traditional pine management. Future research should monitor herpetofauna through succession and consider landscape‐scale effects and other potential feedstock sources. © 2013 The Wildlife Society.